Uptake of tuberculosis prevention therapy in people living with HIV/AIDS in northern Nigeria: a programme to increase use of isoniazid preventive therapy. Issue 1 (April 2020) - Yunusa, Fadimatu; Bello, Maryam; Kayode, Gbenga A; Adegboye, Adeoye; Abone, Geraldine; Murtala-Ibrahim, Fati; Okposo, Martha; Anjorin, Atinuke; Dutt, Saswata; Yusuf, Oche; Sam-Agudu, Nadia; Dakum, Patrick
Abstract: Background: Tuberculosis is a main cause of death in people living with HIV and results in around 39 000 deaths every year in Nigeria. Isoniazid preventive therapy (IPT), the standard tuberculosis preventive therapy used in Nigeria, has been shown to significantly reduce mortality and prevent tuberculosis in people with HIV. Despite efforts and strategies to scale up this treatment in Nigeria, the process has remained very slow. Here we describe a programme to increase IPT uptake in health facilities in four states in northern Nigeria, while also monitoring trends in IPT use with the aim of increasing access for people with HIV. Methods: Data were collected at 90 health facilities in Nasarawa, Kano, and Katsina states and the Federal Capital Territory (FCT), Nigeria, between Oct 1, 2017, and March 31, 2019. A monitoring tool was used to track clinic attendance, IPT eligibility status, and percentage uptake of isoniazid (the proportion of people with HIV starting a 6 month course of isoniazid) in patients with HIV at these health facilities. Baseline data were collected between Oct 1, 2017, and Feb 28, 2018, and identified reasons for low IPT uptake included: stockout of isoniazid, documentation gaps, improper filling of the relevant source documents, and poor clinician awareness of use of IPT. In response to these barriers to uptake, interventions such as folder tagging and electronic prompts of eligible clients prior to clinic visits, clinician sensitisations through training and retraining to raise the awareness of IPT, and active tracking of eligible clients were implemented. We collected post-intervention data from March 1, 2018, to March 31, 2019. Analysis was done using Excel and STATA. Findings: During the 6 month pre-intervention period, 3659 (14%) patients were commenced on isoniazid out of 26 136 eligible patients. In the initial 6 months post-intervention, 18 367 (80%) patients were started on isoniazid out of 22 020 eligible patients. Uptake dropped suddenly in October, 2018, due to stockout of isoniazid. Remedial stock redistribution resulted in a steady increase of isoniazid uptake and a total number of 43 075 patients out of 50 050 patients (86%) commenced isoniazid within the 12 month review period. Interpretation: Capacity building of health-care workers on isoniazid through training and retraining resulted in marked improvements in IPT uptake through: increased health-care worker knowledge about IPT; proper documentation on the relevant source documents and the electronic medical records; and availability, and use of, isoniazid electronic prompts to highlight clients who were eligible for IPT. However, there is a need to strengthen drug logistics, especially in guaranteeing a consistent and adequate supply of isoniazid in all facilities to avoid stockouts, thus ensuring optimum IPT uptake or access for people living with HIV in Nigeria. Funding: Institute of Human Virology, Nigeria